Genetic alteration profiling in middle-aged women acutely exposed during the mechanical processing of dental nanocomposites - Rossnerova, Andrea; Chvojkova, Irena; Elzeinova, Fatima; Pelclova, Daniela; Klusackova, Pavlina; Zdimal, Vladimir; Ondrackova, Lucie; Bradna, Pavel; Roubickova, Adela; Simova, Zuzana; Rossner, Pavel (Environmental toxicology and pharmacology, 2024)
Nanoparticles (NPs) have become an important part of everyday life, including their application in dentistry. Aside from their undoubted benefits, questions regarding their risk to human health, and/or genome have arisen. However, studies concerning cytogenetic effects are completely absent. A group of women acutely exposed to an aerosol released during dental nanocomposite grinding was sampled before and after the work. Exposure monitoring including nano (PM0.1) and respirable (PM4) fractions was performed. Whole-chromosome painting for autosomes #1, #4, and gonosome X was applied to estimate the pattern of cytogenetic damage including structural and numerical alterations. The results show stable genomic frequency of translocations (FG/100), in contrast to a significant 37.8% (p<0.05) increase of numerical aberrations caused by monosomies (p<0.05), but not trisomies. Monosomies were mostly observed for chromosome X. In conclusion, exposure to nanocomposites in stomatology may lead to an increase in numerical aberrations which can be dangerous for dividing cells.
Keywords: zubní materiály; chromozomální aberace; Middle Aged; nanokompozity; Dental Materials; Chromosome Painting; ženské pohlaví; dospělí; Humans; Occupational Exposure; Chromosome Aberrations; malování chromozomů; Female; Adult; pracovní expozice; Nanocomposites; lidé; lidé středního věku